Endometriosis an Ayurvedic View - Jyothi, P K; Drishya, P T (International Research Journal of Ayurveda & Yoga, 2022)
Endometriosis is a chronic estrogen dependent condition characterized by the ectopic implantation of functional tissue lining of uterus. The exact cause of endometriosis is not detected yet even though there are some theories which explain the pathogenesis of endometriosis. Retrograde menstruation and Coelomic metaplasia theories are included under this. Based on the site of appearance classification of endometriosis can be done as pelvic, extra pelvic and remote. Appearance of endometrial tissue in myometrium is termed as adenomyosis and endometriotic deep lesions in ovary is Endometrioma. The risk factor for aggravating endometriosis is cyclical hormonal changes especially estrogen. Ayurveda does not name endometriosis as a separate disease title. In Ayurveda the diseases related with genital tract is discussed under yoniroga. Brihatrayee and laghutrayee describe 20 yoni roga under various dosha vitiation. Due to the peculiar characteristic of pain, generally endometriosis is taken under vatika yoni vyapath. Even though vata is predominant, pitha and kapha dosha are also involved in various stages. Retrograde flow of menstrual blood, genetic factors, lymphatic and vascular spread are considered as the causative factors. Nidana of endometriosis include mithayahara,-vihara, arthava dusti, bija dushti, use of apadravyas (iatrogenic causes) and daiva (genetic or chromosomal factors). Various type pain and infertility are the main clinical features of endometriosis. Pain is due to increased vata in kadee desa. Through the study the Nidana of endometriosis is analyzed and compared with latest theories. Endometriosis is not considered as a life threatening disease it is a life altering disease that require timely diagnosis and treatment. Currently there is no universally acceptable treatment protocol for endometriosis is available.